2016
DOI: 10.1007/s13205-016-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioethanol as useful biofuel through the bioconversion of water hyacinth (Eichhornia crassipes)

Abstract: Water hyacinth (Eichhornia crassipes) represents a promising candidate for fuel ethanol production in tropical countries because of their high availability and high biomass yield. Bioconversion of such biomass to bioethanol could be wisely managed through proper technological approach. In this work, pretreatment of water hyacinth (10 %, w/v) with dilute sulfuric acid (2 %, v/v) at high temperature and pressure was integrated in the simulation and economic assessment of the process for further enzymatic sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 24 publications
1
23
1
3
Order By: Relevance
“…Table 2 compare the found results in this work with the others two researches. Table 2 shows that the obtained yield, in this work, is better than Satyanagalakshmi et al (2011) results, however, is smaller than results found per Das et al (2016), that used two microorganisms for fermentation, S cerevisiae, a yeast normally utilized in alcohol fermentation, and Z. mobilis, one bacteria with more fast fermentation and that show the ethanol yield biggest than with yeast (Ernandes and Garcia-Cruz 2009).…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…Table 2 compare the found results in this work with the others two researches. Table 2 shows that the obtained yield, in this work, is better than Satyanagalakshmi et al (2011) results, however, is smaller than results found per Das et al (2016), that used two microorganisms for fermentation, S cerevisiae, a yeast normally utilized in alcohol fermentation, and Z. mobilis, one bacteria with more fast fermentation and that show the ethanol yield biggest than with yeast (Ernandes and Garcia-Cruz 2009).…”
Section: Resultscontrasting
confidence: 62%
“…When the process time decreases its productivity increases. Satyanagalakshmi et al (2011) and Das et al (2016) used Eichhornia crassipes as raw material by 2G ethanol production; however, both did the biomass pretreatment with sulfuric acid and did not study the SHF process. Table 2 compare the found results in this work with the others two researches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control measures adopted worldwide have exhibited varying extent of success, but complete eradication has not yet achieved (Ray et al 2009;Patel 2012;Stubbs and Kennedy 2012). However, studies have reported that water hyacinth can be a good source of energy owing to the profuse growth and abundance (Mathur and Singh 2004;Gunnarsson and Petersen 2007;Mishima et al 2008;Chuang et al 2011;Das et al 2016). The dry plant biomass mainly comprises of cellulose (18-31%), hemicellulose (18-43%) and lignin (7-26%) Bergier et al 2012;Barua and Kalamdhad 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The high content of carbohydrate can be hydrolysed through acidic and alkaline treatment into fermentable sugars Aswathy et al 2009;Barua and Kalamdhad 2016). Efforts done to tap the biomass as a suitable feedstock for the production of biofuels like biogas (Vivekanand et al 2013;Barua and Kalamdhad 2016), bioethanol (Das et al 2016;Shanab et al 2017), biohydrogen Chuang et al 2011;Lazaro et al 2014) and biodiesel (Shanab et al 2017) have been proved successful O'Sullivan et al 2010;Sharma et al 2016).…”
Section: Introductionmentioning
confidence: 99%